Current Insight into Biological Markers of Depressive Disorder in Children and Adolescents: A Narrative Review - Jana Trebatická; Martin Vatrál; Barbora Katrenčíková; Jana Muchová; Zdeňka Ďuračková (Antioxidants)
Depressive disorder (DD) in children and adolescents is a growing public health concern with a complex and multifactorial etiology. While most biomarker research has focused on adults, increasing attention is being paid to age-specific molecular mechanisms. This narrative review provides a comprehensive overview of current knowledge on potential biomarkers of DD, including genetic, neurotransmitter, hormonal, inflammatory, lipid, and oxidative stress markers, in youth compared to adult populations. Special emphasis is given to findings from the DEPOXIN project (Molecular basis of depressive disorder in children and adolescents, the influence of omega-3 fatty acids and oxidative stress), a multicenter study investigating biological markers in children and adolescents with DD. The project identified significantly increased oxidative stress markers (8-isoprostanes, advanced oxidation protein products, nitrotyrosine) and decreased antioxidant enzyme activity (glutathione peroxidase). Moreover, HDL (high density lipoproteins) cholesterol and its subfractions were negatively correlated with depression severity. At the same time, thromboxane B2, omega-6/omega-3 fatty acid ratios, and salivary cortisol levels showed strong positive correlations with depressive symptoms and biochemical markers of inflammation. These results suggest a distinct molecular profile of depression in paediatric populations, emphasizing the importance of developmental context in biomarker research. The review aims to synthesize existing evidence, compare findings across age groups, and highlight the need for personalized, age-appropriate strategies in the diagnosis and treatment of depressive disorders.